Behavioral differences of individuals with different self-regulation levels in a real-life example of teamwork—DOTA 2 - Wang, Yilin; Leng, Jiexing; Zhang, Yichuan; Chen, Wenwen; Xing, Fugui; Zhao, Nan (Frontiers in Psychology, 2022)
Teamwork is a vital aspect of human life, including a set of concrete behaviors which could be divided into various categories such as task performance, job dedication, backing up behavior, and monitoring. As an essential psychological factor could form team members to adapt to environmental changes, self-regulation has a marked impact on teamwork results. However, why self-regulation could affect results of teamwork in real life and how self-regulation influence the concrete teamwork behaviors remains unclear. This study recorded and extracted participants’ detailed gaming behaviors in DOTA 2, which is an example of real-life teamwork scenario. The sample consisted of 59 DOTA 2 players with relative low-level self-regulation (93.22% male) and 59 with relative high-level self-regulation (96.61% male). Controlling confounding factors, we explored behavioral differences between the two groups in different types of heroes. Results showed that self-regulation influenced specific gaming behaviors including the categories of task performance, job dedication, and backing up behavior, but not including monitoring. Additionally, these impacts of self-regulation varied by hero type. These results demonstrate the different impacts of self-regulation on different categories of teamwork behaviors, and these impacts are considerably determined by individual’s role in the team. These findings shed light on the mechanism of the teamwork performance improvement caused by self-regulation and provide new insights into understanding the different impact patterns of self-regulation in different real-life tasks and responsibilities.